Adrenal insufficiency revealing bilateral adrenal hemorrhage related to JAK2 V617F-positive essential thrombocythemia: about two cases. Issue 3 (20th April 2023) - Gensous, Noémie; Jourde, Wendy; Salles, Kévin; James, Chloé; Guy, Alexandre; Duffau, Pierre
Abstract : Bilateral adrenal hemorrhage is a rare cause of adrenal insufficiency which has been rarely associated with myeloproliferative neoplasms. Here, we report two cases of bilateral adrenal hemorrhage revealed by abdominal pain, malaise, and fatigue in two octogenarian males previously diagnosed with JAK2 V617F-positive essential thrombocythemia. Both patients were on long-term direct oral anticoagulant treatment for atrial fibrillation. Evolution was favorable under steroid replacement therapy, associated with cytoreduction, aspirin, and switch of direct oral anticoagulants for vitamin K antagonists.